Trends in complications and mortality following catheter ablation of atrial fibrillation: results from 22, 582 ablations in Australia and New Zealand from 2010 to 2015. (25th November 2020) - Ngo, L; Ali, A; Ganesan, A; Woodman, R; McGavigan, A; Adams, R; Ranasinghe, I
Abstract: Background: Recent studies from the United States report rising rates of in-hospital complications and mortality following catheter ablation of atrial fibrillation (AF) but whether such a trend is observed in other populations is uncertain. Purpose: To examine the trends in complications and mortality following AF ablations up to 30 days after discharge in Australia and New Zealand (ANZ) using nationwide data. Methods: All patients ≥18y undergoing catheter ablation of AF from 2010–2015 were identified using hospitalisation data from all public and most private hospitals in ANZ. The primary endpoint was one or more procedural complications during the hospital stay or within 30 days of discharge. The secondary endpoints were mortality and other specific complications. Unadjusted trend was evaluated using Cochran-Armitage test while that of complications, adjusting for differences in other characteristics, was evaluated using multivariate logistic regression with the year of ablation modelled as a continuous variable. Results are reported as odd ratios (OR) and 95% confidence intervals (CI). Results: A total of 22, 582 AF ablations were included (mean age 62.2±11.6y, 29.1% female, 94.4% elective procedures). The number of ablations increased by 26.4% during the study period (3, 097 in 2010 to 3, 915 in 2015). Rates of heart failure (8.98% to 10.09%, p for trend=0.010), diabetes (4.52% to 12.46%, p<0.001), chronic kidney disease (2.36% to 4.29%, p<0.001) significantly increased over time but that of hypertension decreased (15.27% to 12.29%, p<0.001). The incidence of overall complications (6.55% in 2010 to 6.67% in 2015, OR 0.99, 95% CI 0.96–1.03) was unchanged during the study period (Figure 1A). When individual complications were considered, mortality rate was low with no statistically significant change with time (0.19% to 0.15%, OR 1.03, 95% CI 0.84–1.28) (Figure 1A) while the rate of acute kidney injury (0.23% to 0.51%, OR 1.17, 95% CI 1.02–1.34) increased and that of venous thromboembolism (0.16% to 0.0%, OR 0.71, 95% CI 0.54–0.94) decreased (Figure 1B). Though the incidence of any bleeding (4.49% to 3.98%, OR 0.97, 95% CI 0.93–1.01) was unchanged, that of major bleeding requiring blood transfusion (0.97% to 0.64%, OR 0.87, 95% CI 0.79–0.96) declined significantly (Figure 1B). No significant trend was observed in other complications or when in-hospital (5.13% to 5.21%, OR 1.00, 95% CI 0.97–1.04) and post-discharge (1.55% to 1.63%, OR 0.97, 95% CI 0.91–1.03) complications were separately evaluated. Conclusions: Though more patients with heart failure, diabetes and chronic kidney disease underwent catheter ablation of AF over time in ANZ, the overall complication rate was unchanged with a significant decrease in the incidences of major bleeding and venous thromboembolism. However, rate of acute kidney injury nearly doubled, and this could be a potential target for efforts to further improve procedural safety. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): The National Heart Foundation of Australia